Sobre o princípio fundamental da contagem - Alves, Vanderli de Araújo (2015)
We presented The Fundamental Principle Count (PFC) as a consequence of the Principle Finite Induction (PIF) and as the application (PFC), we presented the resolution of various problems involving count, arrangements, combinations and permutations. The main objective of this work is to present the logical-mathematical reasoning that involves counting notion avoiding to give the leadership that is customarily given to mathematical formulas. To this end, we solve various problems without using mathematical formulas, giving priority to direct application of the PFC.